The concept of Islamic governance according to HAMKA’s thought / Adibah Abdul Rahim - Abdul Rahim, Adibah (Universiti Teknologi MARA, 2025)
The absence of Islamic governance has brought various implications and challenges to the Muslim societies. Therefore, it is timely and relevant to discuss the need for Islamic governance as an effort to create a societal framework that aligns with Islamic values and principles. This paper explores the concept of Islamic governance according to HAMKA’s perspective which can be considered a significant contribution to the field of Islamic political thought. Although HAMKA did not outline a detailed blueprint for Islamic governance, he proposed its core principles in a holistic manner which include shura, social justice, ethical leadership, and social wellbeing. This study employs a qualitative method based on library research. The data were obtained through various sources, including books, manuscripts, articles, and documents relevant to the topic. The study found that HAMKA’s approach to Islamic governance reflects his attempt to harmonize traditional Islamic principles with the needs and challenges of modern times. His ideas were characterized by his understanding of Islam and his observations of the cultural and historical context of his society.